Aboriginal Women ‘Working’ at Play: Canadian Insights - Paraschak, Vicky; Forsyth, Janice (Ethnologies, 2010)
In this paper, we explore complex ways in which Aboriginal women experience sport. In particular, we examine the gendered dimensions they face in trying to gain recognition and support for their work and volunteering at the community level where their presence is ubiquitous and tangible: sport would not exist for many Aboriginal people if it were not for female labour. What we saw, at the heart of their struggles, are deeply held aspirations that go well beyond ‘women only’ issues to broader concerns tied to the health and wellbeing of the people in their community, specifically the youth.